Selection and Complex Multigene Traits - Hasson, Esteban Ruben (2013)
Phenotypic characters that display continuous variation are usually called ‘quantitative traits’ or ‘complex traits’. Alternatively, geneticists refer to them as ‘multigene traits’, because the underlying genetic architecture is assumed to be polygenic. Analyses of the genetic architecture of diverse quantitative traits suggest that the number of loci (quantitative trait loci, QTLs) affecting trait variation can be very different. Moreover, experimental studies report contrasting genetic architectures, where either large‐effect QTLs or small‐effect QTLs explain most of the phenotypic variation. In addition, recent reports highlight the pervasiveness of epistasis. Considerable evidence, obtained with the QST–FST methodology, supports the idea that natural selection plays a key role in the evolution of complex traits. Nevertheless, the identification of a representative number of genes underlying QTLs is necessary to determine the contribution of selection, drift and gene flow for the evolution of complex traits.